EFFECT OF OPERATING COSTSONAL OPERATING INCOME (BOPO) AND NON-PERFOMING Financing (NPF) ON RETURN ON ASSETS (ROA) IN PT. BANK RAKYAT INDONESIA SYARIAH, TBK FOR THE PERIOD 2009-2017 - ABDUL nasser NASSER; Ali Hardana; erlina erlina (Journal Of Sharia Banking, 2022)
One of the goals of the company is to obtain maximum profit. Based on the published financial statements of PT. Bank Rakyat Indonesia Syariah, Tbk Period 2009-2017. Tend to fluctuate in several quarters, the phenomenon that occurs in this study can be seen from the increase and decrease in Operational Cost and Operating Income and Non-performing Financing that are not in accordance with the increase and decrease that occurs in Return on Assets. The formulation of the problem in this study is whether there is an influence of Operational Costs Operating Income and Non Performing Financing on Return On Assets at PT. Bank Rakyat Indonesia Syariah Tbk, the period 2009-2017 simultaneously. The aim of the study is to determine the effect of the Operational Cost of Operating Income and Non-performing financing on the Return On Assets at PT. Bank Rakyat Indonesia Syariah. Tbk, 2009-2017 period. The discussion of this research is about Operational Costs Operating Income and Non-Performing Financing and is related to other sharia banking fields. In this connection, the approach taken is there relates to Operational Costs, Operational Revenues, and Non-Performing Financing of Return On Assets. This type of research is quantitative research, and the source of the data used is secondary data through www.ojk.go.id. The sample of this study was 36, data analysis used multiple linear regression, descriptive statistics, normality test, linearity test, classical assumption test, hypothesis test, coefficient of determination R2 test, and t-test and F test, and the data were processed with the help of SPSS 23 statistical calculations.  Based on the results of research on operational costs operating income variables have a negative effect on Return On Assets, this is evidenced by the value of - count - table that is (-8,361 -2,03452), then Ho is rejected and Ha is accepted. And the Non-Performing Financing variable influences the Return On Assets with the value of tcount table that is (2.303 2.03452), Ha is accepted and Ho is rejected. Then simultaneously the operational cost of operating income and Non-performing financing variables influence simultaneously on Return On Assets with the value Fcount Ftable (45.210 3.28).